1996
DOI: 10.1007/bf02815106
|View full text |Cite
|
Sign up to set email alerts
|

The possible place of cathepsins and cystatins in the puzzle of Alzheimer disease

Abstract: Lysosomal proteinases (cathepsins) and their endogenous inhibitors (cystatins) have been found to be closely associated with senile plaques, cerebrovascular amyloid deposits, and neurofibrillary tangles in Alzheimer disease (AD). Further, profound changes in the lysosomal system seem to be an early event in "at-risk" neurons of AD brains. There is an ongoing controversy as to whether lysosome-associated proteolytic mechanisms are causally related to the development and/or further progression of the disease. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 112 publications
0
40
0
2
Order By: Relevance
“…The increase in lysosomes is likely an important finding, because abnormalities in lysosomes are considered a prominent morphologic marker of distressed neurons and because lysosomal abnormalities are associated with neurodegenerative diseases (20)(21)(22)(23)(24). Studies have suggested that accumulation of abnormal proteins, as in prion encephalopathies and formation of ␤͞A4 protein from its precursor in Alzheimer's disease, takes place in lysosome-related organelles (24).…”
Section: Atm؊͞؊ Mice Have Increased Numbers Of Lysosomes In Pcs Detecmentioning
confidence: 99%
“…The increase in lysosomes is likely an important finding, because abnormalities in lysosomes are considered a prominent morphologic marker of distressed neurons and because lysosomal abnormalities are associated with neurodegenerative diseases (20)(21)(22)(23)(24). Studies have suggested that accumulation of abnormal proteins, as in prion encephalopathies and formation of ␤͞A4 protein from its precursor in Alzheimer's disease, takes place in lysosome-related organelles (24).…”
Section: Atm؊͞؊ Mice Have Increased Numbers Of Lysosomes In Pcs Detecmentioning
confidence: 99%
“…More specific functions have recently been postulated in a wide range of physiological and pathological processes. These include antigen presentation (3), prohormone processing (4), turnover of ␤-amyloid in Alzheimer's disease (5), tumor invasion (6), tumor angiogenesis (7), and apoptosis (8,9). …”
mentioning
confidence: 99%
“…The enzyme was mainly found in the lysosomes of normal tissues and participates in intralysosomal turnover of cellular proteins and molecules assimilated from the extracellular environment as well as in the degradation of extracellular matrix components, prohormone processing (Shinagawa et al, 1990), and turnover of ␤-amyloids in Alzheimer's disease (Bernstein et al, 1996). Further functions of cathepsin B have been found with the development of cathepsin B-deficient mice.…”
mentioning
confidence: 99%